The serpent's shadow - Lackey, Mercedes (New York : Distributed by Penguin Putnam, 2001)
Dr. Maya Witherspoon, the daughter of a British physician and a Brahmin woman, flees her home in India following the mysterious deaths of her parents in 1909, and sets up practice among the poor of London, but she knows she must find a way to develop the magical powers she inherited from her parents in order to stop the evil that stalks her.
"DAW Books collectors No. 1177"--T.p. verso.
Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Booklist, February 2001.
Books for the Teen Age (NYPL), January 2002.
Keywords: Magic -- Fiction; Women physicians -- England -- London -- Fiction; Women, East Indian -- England -- London -- Fiction; Indians -- Fiction; Magic -- Fiction; Psychological fiction; Women physicians -- London (England) -- Fiction; London (England) -- Fiction; London (England) -- Fiction